Co-designing mHealth technologies with youth: REACH Initiative in Turkey and Lebanon. (30th September 2020) - Karadag Caman, O; Karabey, S; Sumbuloglu, I; Yazbik-Dumit, N; Ben Amor, Y
Abstract: Issue: Many young people face barriers in accessing youth-friendly health information and health care. Differing cultural norms, languages, laws, and stigma pose additional challenges for young refugees in host countries. There is a need to implement more innovative, youth-friendly and widely used solutions to address the health education and health care needs of young people. Description of the practice: REACH (REfugees Act and Communicate for Health) is a regional initiative, which aims to bridge the gap in health literacy and health care access among refugee and local youth via digital technologies in Turkey and Lebanon. Using community based participatory action research (CBPAR) approach, REACH aims to assess the impact of information and communication technologies on accessing health information and services among youth in countries that host large refugee populations. The initiative is supported by TaiwanICDF, Blue Chip Foundation and Columbia University. Results: With a strong youth-adult partnership, the initiative includes stakeholders' meetings, a mixed-methods study (survey and photovoice study with youth, qualitative interviews with service providers and policy makers), photo exhibitions, panels, and production of policy reports and scientific publications. Based on local needs in each country, REACH works with refugee and local youth, software developers, academia, local health authorities, UN organizations and NGOs to develop a multilingual mHealth application to increase health literacy and improve health care access among young refugee and host communities, and aims to assess its effectiveness to contribute to the limited evidence base on using health technologies for youth health promotion in forced migration settings. Lessons: Using CBPAR and co-design approaches and engaging both refugee and local youth in the process of assessing needs and developing mHealth technologies can help to mitigate risks and increase the success rate of interventions. Key messages: Community involvement and empowerment as well as harmonization between refugee and host communities increases the success of health interventions and builds a shared environment in host countries. mHealth solutions can be used for youth health promotion in a cost-effective way, and help in reaching vulnerable or stigmatized youth that struggle with health information and health care access.